1987
DOI: 10.1111/j.1095-8649.1987.tb05771.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal occurrence of the infectious stage of proliferative kidney disease (PKD) and resistance of rainbow trout, Salmo gairdneri Richardson, to reinfection

Abstract: The seasonality of proliferative kidney disease (PKD) in rainbow trout, Salmo gairdneri Richardson. at the American River Hatchery, California was found to be primarily dependent on the presence or absence of the infectious stage in the water supply. This was determined by introducing sentinel trout into the hatchery water supply on a monthly basis, followed by their transfer to the laboratory for subsequent holding in 18" C, pathogen-free water for one month prior to examination. These exposures demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 16 publications
1
64
1
Order By: Relevance
“…Similarly, trout which had recovered from clinical PKD infections were found to be resistant to reinfection. Resistant was induced by active infection and not just previous exposure (Foott & Hedrick, 1987). D. puntazzo recovered from E. leei infection, when challenged with the parasite again were refractive to the disease, indicating possibly the development of immunity against the parasite (Golomazou et al, 2006) This protective specific immune response is probably accompanied by a repertoire of non-specific immune factors.…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…Similarly, trout which had recovered from clinical PKD infections were found to be resistant to reinfection. Resistant was induced by active infection and not just previous exposure (Foott & Hedrick, 1987). D. puntazzo recovered from E. leei infection, when challenged with the parasite again were refractive to the disease, indicating possibly the development of immunity against the parasite (Golomazou et al, 2006) This protective specific immune response is probably accompanied by a repertoire of non-specific immune factors.…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…T. bryosalmonae and S. truttae began spore formation in September and all spores were apparently shed by the following spring. Brown trout acquires immunity towards these species (Foott and Hedrick, 1987 ;McGeorge, 1994). C. schurovi and C. truttae mature spores were first detected in August and over the following winter in 0+ brown trout.…”
Section: Seasonal Occurrence Of Infections and Parasite Locationsmentioning
confidence: 99%
“…Current studies are also examining the efficacy of Fumagillin at these dosages in protecting rainbow trout from continuous exposures to the infectious stage of the parasite. We are interested in this because it has been demonstrated that the infectious stage is present for at least 7 mo of the year at one trout culture site in California (Foott & Hedrick 1987).…”
Section: Experiments Lmentioning
confidence: 99%